Asuhan Keperawatan Pada Klien Dengan Post Debridement Ulkus Diabetes Melitus Di Ruang Gladiol Atas Rumah Sakit Umum Sukoharjo - Handayani, Nur; , Okti Sri Purwanti, S.Kep., Ns., M.Kep., Ns. Sp.Kep.M.B (2015)
NURSING CARE TOCLIENTS WITHPOSTULCER DEBRIDEMENT DIABETES MELLITUS IN THE GLADIOL ROOM REGIONAL GENERAL HOSPITAL SUKOHARJO (Nur Handayani 2015, 54 pages) ABSTRAK Background: Diabetes mellitus is a metabolic abnormalities with the main feature of which is the increase in blood glucose levels, hyperglycaemia. Diabetic foot ulcers is the chronic complications of diabetes mellitus is caused debridement or amputation. Objective: The aim of this scientific work is to be able to understand more about the nursing care post ulcer debridement diabetes mellitus, include: assessment, making nursing diagnosis, planning, nursing actions and evaluate nursing care in patients with diabetes mellitus ulcer debridement post in hospital wards Gladiolus Upper Sukoharjo. Results: after the nursing care for 3 x 8 hours is obtained, complaints of pain in the client decreased from 5 to 2, the absence of signs of infection, the patient's basic needs are met. Conclusion: based on existing cases are able to be enforced three diagnoses of acute pain associated with surgical incision, damage the integrity of the skin associated with diabetes mellitus post ulcer debridement, the risk of infection associated with ulcer debridement post diabetes melitus and third diagnosis of partially resolved. The need for further cooperation between clients, families and health professionals. Keywords: diabetes mellitus, post debridement, pain, skin integrity, the risk of infection.